Impact of information sharing and buyer dependence among supply chain members on trust and strategic flexibility - Kui-ran Shi; Ji-ning Wang; Ping Wang (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
Despite widespread acceptance of the idea that strategic flexibility is critical to the success of firm's operations management, strategic flexibility in supply chain management remains largely unexplored by researchers. To fill this research gap, this study attempt to propose the theoretical model of relationship among information sharing, the buyer's dependence, trust and strategic flexibility in a supply chain. Based on the sample of 145 manufacturing firms in Yangtze River Delta, the empirical test of related hypothesis is examined by multiple regression analysis. The results reveal that information sharing between suppliers and buyers improves their trust. In addition, considering the relationship between buyer dependence and trust, there are significant and negative effects of buyer dependence and its 'influence' dimension on trust. Finally, this study finds that alternatives and influence has significantly negative impact on strategic flexibility while trust and information sharing has significantly positive impact on strategic flexibility. Consequently, information sharing has a direct and indirect influence on strategic flexibility. These findings suggest the firm should pay emphasis on the evaluation of information sharing and supplier influence and enhance trust relationship between suppliers and buyers.
Keywords: 650; Information sharing; Buyer dependence; Trust; Strategic flexibility